Extrapolated Economic Loss and Fiscal Sustainability: The Effect of Public Corruption in Peru (2014-2019, 2021-2023) - Flores Coapaza, Paul Alexandro (2024)
This study examines the extrapolated economic damage and its relationship with total non-financial expenditure, fiscal deficit, and public debt in Peru between 2014-2019 and 2021-2023. It explores the conceptual and empirical relationship between public corruption and fiscal sustainability. Sub-sequently, the calculation of extrapolated economic damage within the National Government is detailed, providing an approximate figure of the economic losses caused by corruption and the impact on public assets. Next, an analysis of the relationship between total non-financial expenditure, fiscal deficit, and public debt with extrapolated economic damage in Peru from 2014-2019 and 2021-2023 is presented, broken down into three main aspects: (i) the relationship between the government’s total non-financial expenditure and extrapolated economic damage during the period; (ii) the relationship between the economic results of non-financial public sector operations and extrapolated economic damage; and (iii) the relationship between the balance of non-financial public sector debt and extrapolated economic damage.These indications highlight the inherent complexity of fiscal dynamics, requiring the inclusion of a broader set of variables and greater data accuracy to fully capture the multifaceted effects of public corruption on fiscal sustainability. This aligns with empirical evidence suggesting its influence, while emphasizing the need for more rigorous and nuanced analytical approaches to better understand the interaction.